Pengaruh Keaktifan Berorganisasi Dan Motivasi Belajar Terhadap Prestasi Akademik - Ade Rahmat; Askolani Askolani; Kusuma Agdhi Rahwana (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This study aims to determine the simultaneous and partial effect of Organizational Activeness and Learning Motivation on Academic Achievement of Management Students at Ormawa Faculty of Economics and Business, Universitas Perjuangan Tasikmalaya for the 2022-2023 period. The research method used in this research is quantitative research methods with questionnaires, The population in this study was 37 Management Students at the Ormawa Faculty of Economics and Business, Universitas Perjuangan Tasikmalaya for the 2022-2023 period. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis tools using SPSS version 25 software. The results of the study showed that organizational activity and learning motivation simultaneously had a significant effect on academic achievement. Partial Organizational Activeness has a significant effect on Academic Achievement. Learning motivation partially has a significant effect on academic achievement.